Awake Uniportal VATS for the Evacuation of an Extensive, Superinfected Hemothorax in a Patient with Advanced Mediastinal SMARCA4-Deficient Tumor - Lobinger, Dominik; Reiche, Alicia; Hiebinger, Andreas; Bodner, Johannes (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Background The so-called nonintubated or awake video-assisted thoracoscopic surgery (NIVATS) is performed on spontaneously breathing patients, which was shown to reduce postoperative complications and shorten hospital stay.Case Description Awake uniportal VATS was indicated for the evacuation of an extensive, superinfected hemothorax with symptomatic mediastinal shift in a patient with advanced mediastinal SMARCA4-deficient tumor and declined condition, who did not allow a general anesthetic procedure and was not a candidate for extensive surgery.Conclusion This short microinvasive intervention was a prerequisite to stabilize the threat to the patient's life and thus potentially enable any further tumor-specific therapy.
Keywords: thoracic surgery; mediastinal tumor; minimally invasive surgery; pathology; pleural disease; thoracoscopy/VATS